Whole-genome resequencing landscape of adaptive evolution in Relict gull (Larus relictus) - Chao Yang; Qingxiong Wang; Kuo Sun; Lei Luo; Hao Yuan; Xuejuan Li; Yuan Huang; Hong Xiao (BMC Genomics)
Abstract Background The relict gull (Larus relictus, Charadriiformes, Laridae) classified as vulnerable in the IUCN Red List is defined as a first-class national protected bird in China. However, our knowledge of the evolutionary history of L. relictus is limited. Here, we performed whole-genome resequencing of L. relictus (n = 14) and L. brunnicephalus (n = 3) to explore the genetic relationships and population structures and understand their adaptive evolution. Results The whole genome resequencing generated 667.55 Gb clean reads with an average sequencing depth of ~ 29×. The genomic variant analysis identified 13,717,267 heterozygous SNPs in the samples obtained from 17 individuals. Population genetic diversity analysis revealed that low nucleotide diversity (0.00029) and no obvious population structure in L. relictus. Demographic history revealed that from 180 to 5 kya (thousand years ago), the effective population size (Ne) of L. relictus exhibited declines (24,000 to 5,000), with a very low range population size (2,200 to 5,000). In contrast, from 100 to 80 kya, L. brunnicephalus peaked in ancestral Ne, followed by distinct declines at ~ 70 kya (100,000 to 16,000). The findings identified several genes associated with the correlated changed life-history traits of L. relictus, including BMP4 involved in beak adaptation; HAND2, NEUROG1, COL11A2, and EDNRB involved in the evolution of the palate, soft palate, and tongue; PIGR and PLCB2 involved in an enhanced response to bitter taste by sensing chemical secretions released by staple food substrate insects to activate protective mechanisms. Furthermore, thirty-four genes related to sperm development and activity, including KLHL10 and TEKT3, were identified in the expanded gene family. In addition, MED1, CNOT9, NR5A1, and PATZ1 were involved in enhanced male hormone secretion and a high density of candidate genes associated with embryonic development were identified. The findings indicated that the L. relictus population was in a male-biased diffusion mode; the function of the TEKT3 gene showed that males played a dominant role in brooding, which enhanced their attraction to females. Our study revealed that significant enrichment of olfactory signaling pathway genes, including OR14C36, OR14J1, OR14I1, and OR14A16; inner ear development-related, including PTN, PTPN11, GATA2, ATP8B1, and MYO15A; and those related to hypoxic adaptation to high-altitude breeding and iris colour. Conclusions Based on the results and the knowledge of this organism biology and habitat use, we infer that less adaptive evolutionary pressure on vision in L. relictus were related with their feeding behaviour and adaptation. In summary, this comprehensive analysis provides insights into the evolutionary features of L. relictus and a new perspective for scientific research on L. relictus to effectively determine its future survival viability.